[Ru(Bi8)2]6+ - A cluster in a highly disordered crystal structure is the key to the understanding of the coordination chemistry of bismuth polycations - Groh, Matthias F.; Isaeva, Anna; Frey, Christoph; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2013)
Black platelets of Bi39.67(7)Ru2Br35.0(2) were crystallized from a melt of Bi, BiBr3, and Ru. In the tetragonal crystal structure [P4/mbm, a = 1311.92(6) pm, c = 3018.2(4) pm at 155(5) K], cluster cations [(Bi82+)Ru2+(Bi 82+)] are embedded in a matrix of disordered bromido-bismuthate(III) groups. A thorough analysis of the disorder in the anionic part enabled the unambiguous assignment of the cluster charge. The η4-coordination of the two Bi82+ square antiprisms to the RuII atom in the sandwich complex resembles the bonding of Bi5+ and Bi82+ in the clusters [(Bi5+)Ru+(Bi4Br 4)Ru+(Bi5+)] and [(Bi 82+)Ru+(Bi4Br4)Ru +(Bi5+)] as well as of Bi4 2- in1∞[(Bi42-)Ru+(Bi 4Br4)Ru+]. By combining crystal chemical considerations for all mentioned compounds and using quantum chemical calculations, a common bonding scheme for the coordination compounds of bismuth polycations and polyanions was established. The η4-coordinating bismuth polycations and polyanions act as six electron donors, comparable to nido-carborane ligands, Zintl anions E94- and E 56- (E = Si to Pb), cyclopentadienyl ligands, or the cyclobutadiene dianion. The electron count for the transition metal is 18 in all finite clusters. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bismuth; Cluster compounds; Polycations; Ruthenium; Sandwich complexes